By promoting growth and development, castor bean meal biofertilizer improves the yield and quality of Tartary buckwheat and indirectly improves the growth and development of Tartary buckwheat sprouts - Mingjing, Li; Xuemei, Hu; Rui, Luo; Chunhua, Zhang; Ruimei, Hu; Guibin, Xue; Guorui, Li; Jianjun, Di; Cheng, Wang; Xiaohui, Gu; Zhimin, Su; Ruxin, Li; et al. (Frontiers in Plant Science, 2025)
IntroductionFertilizer selection and application is closely related to crop yield and quality. Tartary buckwheat is a medicinal and food crops, has a broad space for development. However, the effect of castor bean meal biofertilizer on the growth and development, yield and quality of Tartary buckwheat and Tartary buckwheat buds is not clear. The aim of this study was to elucidate the effect of castor bean meal biofertilizer on Tartary buckwheat yield and quality, and then to elucidate the effect of castor bean meal biofertilizer indirectly on Tartary buckwheat bud yield and quality.MethodsTong buckwheat 3 as the test material, in 2 years of field trials, no fertilizer, chemical fertilizer and cow manure as a control, a total of 10 types of fertilizer treatment, respectively, CK (0 kg·ha-1), F1, F2, F3 (fertilizer, 225, 300, 375kg·ha-1); N1, N2, N3 (cow manure, 7500, 15000, 22500kg·ha-1); B1, B2, B3(Castor bean meal biofertilizer, 7500, 15000, 22500kg·ha-1).Results(1) under different fertilizer treatments, Tartary buckwheat plant height, stem thickness, the number of main stem nodes, the number of main stem branches, leaf area and chlorophyll content; single plant grain weight, thousand grain weight and yield of castor bean meal biofertilizer treatment is good, and in the B2 treatment to reach the maximum value. (2) under different fertilizer treatments, Tartary buckwheat protein, starch, cellulose, fat, flavonoid fractions and bioflavonoids are B2 treatment when the highest content. (3) Different fertilization treatments of Tartary buckwheat cultivated Tartary buckwheat buds bud length, fresh weight and dry weight there are significant differences. Tartary buckwheat buds in the 0-16d free amino acids, soluble sugars, total phenols, vitamin C and bioflavonoids content of Tartary buckwheat seeds in the B2 treatment of Tartary buckwheat cultivated Tartary buckwheat buds of the best indicators.DiscussionIn short, this study provides a new fertilization option to improve Tartary buckwheat yield and quality.